Comparison of Examination Results of Cytocentrifuge Cytology and Cell Block Methods on Pleural Fluid Confirmed with Calretinin Immunohistochemistry as Mesothelial Cell Marker - Fitri Desimilani, Fitri Desimilani; Mariedina, Causa Trisna; Betty, Betty; Soekimin, Soekimin; Chrestella, Jessy (Majalah Patologi Indonesia, 2025)
Background Pleural effusion is an abnormal accumulation of fluid in the pleural cavity, which occurs as a result of disturbance in the balance between production and reabsorption. Cytologycal examination is important as diagnosis, determining the stage, guiding further treatment for malignancy. Effusion fluid is often processed using cytocentrifuge cytology or cell block methods which have their advantages and disadvantages. Calretinin as mesothelial cell marker valuable for establishing a more definitive cytopatholgical diagnosis. Methods Analytic observational study with a cross-sectional approach of 49 samples cytologically diagnosed pleural fluid specimens at private hospital in Medan. Examination method cytocentrifuge cytology and cell block followed calretinin immunohistochemistry. Data analysis was tested with Chi-square test. Results The result of pleural effusion examination were confirmed by calretinin immunohistochemistry, which showed positive mesothelial cell in 45 cases (91,8%), while those who did not show or negative mesothelial cell were 4 cases (8,2%). Conclusion There was a significant different between the result of the cytocentrifuge cytology and cell block methods with a p-value < 0,001.